Building the Past : Prehistoric Wooden Post Architecture in the Ohio ValleyGreat Lakes - Genheimer, Robert A.; Redmond, Brian G. (Brian Gerald), 1958- (Book collections on Project MUSE., 2015)
This volume presents the most current research on domestic, public, and ritual architecture created over four millennia ago along the Ohio River, its tributaries, and the adjacent lower Great Lakes.